Radical SAM Enzymes and Ribosomally‐Synthesized and Post‐translationally Modified Peptides: A Growing Importance in the Microbiomes - Benjdia, Alhosna; Berteau, Olivier (Frontiers in Chemistry, 2021)
To face the current antibiotic resistance crisis, novel strategies are urgently required. Indeed, in the last thirty years, despite considerable efforts involving notably high-throughput screening and combinatorial libraries, only few antibiotics have been launched to the market. Natural products have significantly contributed to the discovery of novel antibiotics, chemistry and drug leads with more than half anti-infective and anti-cancer drugs approved by the FDA being of natural origin or inspired by natural products. Among them, thanks to their modular structure and simple biosynthetic logic, ribosomally-synthesized and post-translationally modified peptides (RiPPs) are promising scaffolds. In addition, recent studies have highlighted the pivotal role of RiPPs in the human microbiota, which remains an untapped source of natural products. In this review, we report on recent developments in radical SAM enzymology and how these unique biocatalysts have been shown to install unique and sometimes unprecedented post-translational modifications with a special focus on enzymes originating from various microbiomes.